Scraps of Hope in Banda Aceh Gendered Urban Politics in the Aceh Peace Process - Jauhola, Marjaana (Pro et Contra, 2020)
Scraps of Hope in Banda Aceh examines the rebuilding of the city of Banda Aceh in Indonesia in the aftermath of the celebrated Helsinki-based peace mediation process, thirty years of armed conflict, and the tsunami. Offering a critical contribution to the study of post-conflict politics, the book includes 14 documentary videos reflecting individuals' experiences on rebuilding the city and following the everyday lives of people in Banda Aceh. Marjaana Jauhola mirrors the peace-making process from the perspective of the 'outcast' and invisible, challenging the selective narrative and ideals of the peace as a success story. Jauhola provides alternative ways to reflect the peace dialogue using ethnographic and film documentarist storytelling. Scraps of Hope in Banda Aceh tells a story of layered exiles and displacement, revealing hidden narratives of violence and grief while exposing struggles over gendered expectations of being good and respectable women and men. It brings to light the multiple ways of arranging lives and forming caring relationships outside the normative notions of nuclear family and home, and offers insights into the relations of power and violence that are embedded in the peace.